The Ongoing French Reception of the Objectivists - Abigail Lang (Association Française d'Etudes Américaines, 2017)
For almost fifty years, the Objectivists have been an enduring reference in French poetry, or at least for that section of French poetry committed to the modernist legacy. From the 1968 publication of Serge Fauchereau’s Lectures de la poésie américaine to the documentary poetics of the post-poets, every generation has refashioned the Objectivist canon and critical meaning according to their different, at times antagonistic, needs. Focusing on issues of poetic theory, this paper brings out the landmarks and articulations of the French reception of the Objectivists and shows how the controversies attending the interpretations of Objectivist poetics served to clarify and advance certain issues of French poetics. More generally, it sheds light on the complex dynamics of textual circulation, reception and canonization.